Additional seizure reduction by replacement with Vagus Nerve Stimulation Model 106 (AspireSR). (18th January 2020) - Kawaji, Hiroshi; Yamamoto, Takamichi; Fujimoto, Ayataka; Uchida, Daiki; Ichikawa, Naoki; Yamazoe, Tomohiro; Okanishi, Tohru; Sato, Keishiro; Nishimura, Mitsuyo; Tanaka, Tokutaro; Namba, Hiroki
Highlights: AspireSR is a novel vagus nerve stimulation device. Seizure reduction rate by device replacement from preceding systems to AspireSR was investigated. Seizure frequency significantly reduced after device replacement. Abstract: AspireSR is a novel vagus nerve stimulation (VNS) device which detects ictal heart rate changes and automatically apply additional stimulus. We investigated the difference of the efficacy between AspireSR and preceding VNS models in patients with device replacement. We retrospectively reviewed the clinical data of 17 patients whose VNS devices were changed because of battery discharge. The rates of seizure reduction, the number of antiepileptic drugs (AEDs) used and device parameters between the two devices were evaluated. AspireSR improved significantly the rates of seizure reduction of the patients. Four patients out of 11 patients with low response to the preceding VNS models (no change or <50 % reduction) achieved>50 % seizure reduction. The AEDs used were not different in the observed periods. The device parameters were low setting in AspireSR compared to preceding VNS models. AspireSR decrease significantly seizure frequencies compared to the preceding VNS models. Change of the devices to AspireSR at the time of battery empty could be recommendable.